2021
DOI: 10.15446/revfacmed.v69n3.81603
|View full text |Cite
|
Sign up to set email alerts
|

VIPoma: a rare cause of diarrhea. A case report

Abstract: Introducción. El tumor secretor de péptido intestinal vasoactivo o VIPoma es un tumor funcional neuroendocrino pancreático (F-PNET) raro caracterizado por diarrea secretora, hipokalemia e hipoclorhidria. Su baja incidencia y alto riesgo de malignidad representan un reto clínico que requiere un alto grado de sospecha clínica. Presentación del caso. Mujer de 61 años quien consultó al servicio de urgencias de un hospital de tercer nivel en Medellín, Colombia, por diarrea crónica (7 meses) que llevó a deshidrataci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Although novel agents such as sunitinib were proven to be effective in controlling the symptoms of VIPoma, we did not try them in our case. The poor prognosis of VIPoma is associated with histological grade, staging, and the presence of metastasis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although novel agents such as sunitinib were proven to be effective in controlling the symptoms of VIPoma, we did not try them in our case. The poor prognosis of VIPoma is associated with histological grade, staging, and the presence of metastasis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recientemente, en países desarrollados, se realiza una prueba de ELISA, que no requiere extracción previa, siendo esta la metodología en este estudio. Hasta ahora, en nuestro país no se dispone de la medición de VIP en forma rutinaria, y este caso demuestra su utilidad tanto para confirmar el diagnóstico así como también el seguimiento (Azizian et al, 2021;Sánchez-Salazar et al, 2021).…”
Section: Tumores Secretores De Vipunclassified
“…In 2021, Sánchez-Salazar et al 6 reported a 61-year-old woman with chronic secretory diarrhea, dehydration, and metabolic imbalances. An MRI confirmed a pancreatic mass, chromogranin A levels were elevated, and VIP levels were high.…”
mentioning
confidence: 99%
“…VIPoma, with an incidence of 1 in 10 million individuals per year, 6 is characterized by persistent secretory diarrhea. Early diagnosis curtails complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation

Pancreatic VIPomas From Colombia

Román González,
Padilla Zambrano,
González
et al. 2023
Pancreas